Hypoxic Coma Due to Takotsubo Syndrome after Toxic Carbon Monoxide Poisoning - Formisano, Rita; Greco, Cesare; Aloisi, Marta; Contrada, Marianna; Caravasso, Chiara Falletta; Luccichenti, Giacomo; Buzzi, Maria Gabriella (Archives of Clinical and Medical Case Reports, 2020)
Objectives: Takotsubo syndrome (TS) is clinically characterized as an acute coronary syndrome with rapid development and subsequent resolution of severe, reversible left ventricular dysfunction. We describe a case of TS induced by an acute, severe reduction of oxygen supply resulting in a life threatening carbon monoxide poisoning and leading to coma. A 58 year-old woman was referred to Emergency Room (ER) with cardiogenic shock and hypoxic coma. Materials and Methods: At ER admission, the Glasgow Coma Scale score was 5 and she needed intensive cardio-pulmonary support and mechanical ventilation. A malfunctioning of the heating system in her bedroom was demonstrated, thus the diagnosis of carbon monoxide poisoning was applied. After a first recovery of consciousness, her responsiveness progressively worsened to a new coma occurrence as by a delayed leukoencephalopathy. At admission in rehabilitation, the patient was diagnosed as vegetative state/unresponsive wakefulness syndrome, according to the Coma Recovery Scale-Revised. After intensive multidisciplinary rehabilitation, the patient evolved from Minimally Conscious State Minus (akinetic mutism) to MCS Plus and finally emerged to Exit-MCS. At 9 months follow-up, the patient recovered a complete autonomy in daily living activities. This is the first case report of TS after toxic carbon monoxide poisoning.